Anti-Bullying Seminar as a Community Service Model: University Students’ Engagement in Fostering Safe School Environments for Elementary School Children in Cidokom Village - Miftah Hur Rahman Zh; Athia Nur Kamilah; Muhibuddin Fadhli; Ferry Irawan Febriansyah; Afiful Ikhwan; Hendro Risbiyantoro (Jurnal Pengabdian Masyarakat (Bisma), 2025)
Bullying remains a pervasive concern in Indonesian elementary schools, with approximately 30% of reported cases occurring at the primary education level. This community service study examines the implementation and effectiveness of an anti-bullying seminar conducted by university students from Universitas Darunnajah for elementary school children in Cidokom Village, Bogor Regency. The program employed a participatory action approach that integrated interactive seminars, role-playing activities, and psychoeducational workshops, targeting 85 students in grades 4 through 6. Pre-test and post-test assessments were administered to measure changes in students’ knowledge of how to identify bullying, empathy levels, and intentions to intervene as bystanders. Descriptive statistical analysis, supplemented by qualitative observational data, revealed significant improvements across all measured indicators. Students’ knowledge of bullying types and recognition increased from a mean score of 52.4 to 78.6, while empathy scores improved from 48.7 to 74.2. Bystander intervention intentions rose from 45.3 to 76.8. Qualitative findings indicated heightened student engagement and increased willingness to report bullying incidents. This study contributes to the growing body of literature on university-community partnerships in bullying prevention. It demonstrates the viability of student-led community service programs as vehicles for promoting safe school environments in rural Indonesian communities.